Programa de reeducación en la lectura y escritura a través del método silábico para niños de 7 a 11 años del Programa Acción Guambras Centro de Referencia Mi Patio, 2017-2018. - Espinoza Toscano, Ana Karen (2018)
The present systematization describes the experience of the intervention project called “Programa de Reeducación en la Lectura y Escritura a través del Método Silábico para niños de 7 a 11 años del Programa Acción Guambras Centro de Referencia Mi Patio, 2017-2018” This program is the result of the diagnosis made at the Institution, which is determined by the needs of the population addressed, where literacy was identified as a latent problem, it was evaluated with T.A.L.E. of Josep Toro and Montserrat Cervera that allowed to determine the general levels and the specific characteristics of reading and writing in children who are in learning process. The results obtained through the application of T.A.L.E., allowed to develop a variety of activities based on the syllabic method that allowed children to integrate letters, syllables, words, texts, copy, dictation and spontaneous writing. After the implementation of the reeducation of reading and writing program, T.A.L.E. was again applied, making it possible to demonstrate the progress and achievements that each child acquired. Keywords: Reeducation, literacy